Occurrence of Corynebacterium ulcerans and Pasteurella multocida in pet cats and dogs in Klang Valley, Malaysia - Ng, Geok Lim (2015)
Pets especially cats and dogs are reservoirs for Corynebacterium ulcerans and Pasteurella multocida. Corynebacterium ulcerans can produce diphtheria toxin and cause diphtheria-like symptoms in human. It is an emerging public health threat in developed countries, with incidence sometimes higher than that of C. diphtheriae. Pasteurella multocida is often associated with bite wounds and scratches which causes infections that lead to significant morbidity and mortality in humans. Therefore, this study was carried out to determine the occurrence of C. ulcerans and P. multocida in pet cats and dogs in Klang Valley, Malaysia and their antibiotic resistance profiles. Nasal and pharyngeal samples were collected from apparently healthy animals consisted of 26 cats and 29 dogs which were presented in four veterinary health care facilities in Klang Valley. The isolates were tested against six antibiotics commonly used in small animal practice. Corynebacterium ulcerans was not isolated (0%) in this study whereas the occurrence for P. multocida was low (10.9%). Low antibiotic resistance were observed for amoxicillin-clavulanic acid, tetracycline, trimethoprim-sulfamethoxazole and cephalexin in P. multocida isolates (16.7% each). This study demonstrated the zoonotic risks associated with pet cats and dogs and awareness among pet owners appears to be necessary. The current study is the first description of the isolation and antibiotic resistance profile of C. ulcerans and P. multocida in pet cats and dogs in Malaysia.